In vitro Culture of Naïve Human Bone Marrow Mesenchymal Stem Cells: A Stemness Based Approach - Pal, Bidisha; Das, Bikul (Frontiers in Cell and Developmental Biology, 2017)
Human bone marrow derived mesenchymal stem cells (BM-MSCs) resides in their niches in close proximity to hematopoietic stem cells (HSCs). These naïve MSCs have tremendous potential in regenerative therapeutics, and may also be exploited by cancer and infectious disease agents. Hence, it is important to study the physiological and pathological roles of naïve MSC. However, our knowledge of naïve MSCs is limited by lack of appropriate isolation and in vitro culture methods. Established culture methods use serum rich media, and serial passaging for retrospective isolation of MSCs. These primed MSCs may not reflect the true physiological and pathological roles of naive MSCs (Figure 1). Therefore, there is a strong need for direct isolation and in vitro culture of naïve MSCs to study their stemness (self-renewal and undifferentiated state) and developmental ontogeny. We have taken a niche-based approach on stemness to better maintain naïve MSCs in vitro. In this approach, stemness is broadly divided as niche dependent (extrinsic), niche independent (intrinsic) and niche modulatory (altruistic or competitive). Using this approach, we were able to maintain naïve CD271+/CD133+ BM-MSCs for 2 weeks. Furthermore, this in vitro culture system helped us to identify naïve MSCs as a protective niche site for Mycobacterium tuberculosis, the causative organism of pulmonary tuberculosis. In this review, we discuss the in vitro culture of primed vs. naïve human BM derived MSCs with a special focus on how a stemness based approach could facilitate the study of naïve BM-MSCs.